2016
DOI: 10.3171/2016.4.jns16641
|View full text |Cite
|
Sign up to set email alerts
|

Case series of ventriculopleural shunts in adults: a single-center experience

Abstract: OBJECTIVE The peritoneal cavity is widely used as the destination of choice for cerebrospinal fluid shunts. Various alternative sites have been used, particularly in the presence of certain contraindications. The pleural cavity has been used; however, a paucity of evidence details ventriculopleural (VPL) shunt survival, complication, and revision rates in adults. The aim of this study was to present a single center's experience with VPL shunts, identifying complication, revision, and survival rates. METHODS A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…A smaller single‐centre case series reported on 19 adult patients who received VPL shunting—at five‐year follow‐up, three pleural effusions were diagnosed, of which two were symptomatic and required surgical revision. This suggests an 11% incidence of pleural effusions in adult hydrocephalic patients [14]. This differs from Hoffman et al who demonstrated a pleural effusion prevalence of 20% in 59 children undergoing VPL shunt insertion [15].…”
Section: Discussionmentioning
confidence: 97%
“…A smaller single‐centre case series reported on 19 adult patients who received VPL shunting—at five‐year follow‐up, three pleural effusions were diagnosed, of which two were symptomatic and required surgical revision. This suggests an 11% incidence of pleural effusions in adult hydrocephalic patients [14]. This differs from Hoffman et al who demonstrated a pleural effusion prevalence of 20% in 59 children undergoing VPL shunt insertion [15].…”
Section: Discussionmentioning
confidence: 97%
“…The pleura is also not a good option for long term distal catheter placement. 3) Of course, placement in the atrium can also have complications similar to other distal placements; obstruction, infections, and malfunction can occur. However, in a recent comparative study on long term outcome of VPS, the incidence of complications of VAS is not higher than VPS.…”
Section: Discussionmentioning
confidence: 99%
“…Ventriculoatrial shunting may be complicated by migration into the pericardium to cause cardiac tamponade or into the pulmonary system to create a bronchovenous fistula as late as 5 years after initial shunt implantation 21 , 22 . With regard to ventriculopleural shunts, complications described include pleural effusion, pneumothorax, hydrothorax, intrapleural pseudocysts, cardiac tamponade with heart failure, respiratory failure, or trapped lung 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. A case report from 1962 described a patient with a ventriculopleural shunt who presented with severe headache in addition to long-standing irritating and constant desire to cough for several weeks.…”
Section: Discussion Resume Herementioning
confidence: 99%